Writing ability in children with cerebral palsy after phased fibrotomy - Arsić, Dragutin (PONS - medicinski časopis, 2014)
Writing ability is a complex that includes a variety of skills and activities that must be in writing in the interaction. Successful writing is achieved only if all the skills and all of these processes work, and if in the course of learning, or acquisition of writing skills reach their full integrativity. Cerebral palsy does not have a typical clinical picture, but it is specific to each individual in relation to: the etiology of brain damage, localization and size of defects, the period in which the damage occurred. Given this fact assessment of a child with cerebral palsy should be based on the model estimates the potential and profile through achievements in certain areas, the qualitative and quantitative interpretation. The aim of this study is to assess the writing skills of boy who had undergone surgery of stage fibrotomy. The research results indicate that there is a visible improvement in writing skills after the completion of stage fibrotomy intervention (especially after the third intervention). Keywords: cerebral palsy, graphomotor skills, writing, phased fibrotomy